2018
DOI: 10.1089/fpd.2017.2409
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology ofListeria monocytogenesin China

Abstract: Listeria monocytogenes, a ubiquitous bacterium in nature, can lead to human listeriosis through food consumption. Listeriosis is a rare, preventable, and treatable foodborne disease but can cause hospitalizations and fatalities. We reviewed the literature published in China to better understand the prevalence of L. monocytogenes in food products, incidence of human listeriosis, and characteristics of L. monocytogenes strains in China. The average prevalence of L. monocytogenes in Chinese food products in 28 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
70
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 70 publications
8
70
1
Order By: Relevance
“…A similar trend was observed in the current study with occurrence of 2.4% in meat and 1.3% in seafood. The occurrence of L. monocytogenes in raw meat, milk, and cheese in this study was lower than that found in other countries [4,11,16,[39][40][41][42][43][44][45]. The global L. monocytogenes population diversity in the implicated food vehicles could be attributed to several factors: (i) improvements in detection methodologies, (ii) packing facility, (iii) increases in populations of lactic acid bacteria, yeasts, and molds that might have an impact on the microenvironment supporting growth of L. monocytogenes, (iv) period and temperature degree of the storage condition, (v) handling by the consumers, (vi) unhygienic conditions, (vii) uncontrolled temperature, (viii) glove/hand issues, (ix) environmental (hygienic conditions of the farms, hygienic conditions of the slaughter houses, rodents, workers, the slicer, trash handling, and cleanup operations) contamination and subsequent cross contamination to other products, (x) transport, (xi) in the processing facilities, and (xii) during handling at the outlets.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…A similar trend was observed in the current study with occurrence of 2.4% in meat and 1.3% in seafood. The occurrence of L. monocytogenes in raw meat, milk, and cheese in this study was lower than that found in other countries [4,11,16,[39][40][41][42][43][44][45]. The global L. monocytogenes population diversity in the implicated food vehicles could be attributed to several factors: (i) improvements in detection methodologies, (ii) packing facility, (iii) increases in populations of lactic acid bacteria, yeasts, and molds that might have an impact on the microenvironment supporting growth of L. monocytogenes, (iv) period and temperature degree of the storage condition, (v) handling by the consumers, (vi) unhygienic conditions, (vii) uncontrolled temperature, (viii) glove/hand issues, (ix) environmental (hygienic conditions of the farms, hygienic conditions of the slaughter houses, rodents, workers, the slicer, trash handling, and cleanup operations) contamination and subsequent cross contamination to other products, (x) transport, (xi) in the processing facilities, and (xii) during handling at the outlets.…”
Section: Discussioncontrasting
confidence: 78%
“…The general low prevalence of L. monocytogenes of less than one percent detected within this study is lower than previous studies, which reflects increased awareness, vigilance, and good practices in food preparation in the Egyptian community in the area of study [3,9,11,[36][37][38][39][40][41]. A recent study by Leong et al [42] of small food businesses in Ireland showed a similar decrease over the course of a three-year study.…”
Section: Discussionsupporting
confidence: 40%
“…CC3 is one of the most common clones in all regions, while CC9 of the lineage II was shown to be the third largest in Europe and the Western Hemisphere [31]. The predominant clonal complexes in China are CC9 and CC8 in food and ST87 in clinics [53,54]. In the last decade, CC6 noticeably increased in significance as a causative agent of human listeriosis in Africa, Europe, and North America [31,33,[55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…The most predominant STs in contaminated foods were ST1, ST5, ST8, and ST9. 13,[21][22][23][24][25][26] An investigation on the prevalence of L. monocytogenes in retail foods showed that ST9 (23.3%), ST155 (16.4%), and ST8 (12.3%) were the main dominant types in Zhejiang province. 27 Their observations combined the results from this work imply the epidemiological difference between clinical and food isolates from Zhejiang province, although prevalent serotypes 1/2a, 1/2b, and 4b were also identified in that study.…”
Section: Discussionmentioning
confidence: 99%